2014
DOI: 10.5541/ijot.513
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Solubility of Dihydroxybenzoic Acid and Methylbenzoic Acid Isomers in Supercritical Carbon Dioxide

Abstract: In this work, we propose to correlate and predict the solubility in supercritical CO 2 of disubstituted aromatic isomers of hydroxybenzoic acid and methylbenzoic acid with a new methodology based on the expanded liquid theory, in which the solid-fluid equilibrium is modeled using the local composition model of UNIQUAC in which the interaction parameters are related to the solvent reduced density with an empiric exponential form equations. The experimental solubility of hydroxybenzoic acid isomers, methylbenzoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This is also contributed due to the dipole moment of the bioactive compounds where SIN has lower dipole moment about 3.3584 D compared to ISO (4.9035 D) as optimized by the software. Nasri et al (2014) reported a similar pattern in which o-hydroxybenzoic acid (2.65 D) has a higher solubility than p-hydroxybenzoic acid (2.76 D). Johannsen and Brunner (1994) were revealed that the solubility of theophylline was higher than theobromine.…”
Section: Solubility Datamentioning
confidence: 75%
“…This is also contributed due to the dipole moment of the bioactive compounds where SIN has lower dipole moment about 3.3584 D compared to ISO (4.9035 D) as optimized by the software. Nasri et al (2014) reported a similar pattern in which o-hydroxybenzoic acid (2.65 D) has a higher solubility than p-hydroxybenzoic acid (2.76 D). Johannsen and Brunner (1994) were revealed that the solubility of theophylline was higher than theobromine.…”
Section: Solubility Datamentioning
confidence: 75%
“…Experimental determination of solute solubilities in supercritical carbon dioxide at each operating conditions including different temperature and pressure is onerous and time consuming [20,24].…”
Section: The Modeling Of Solubility In Supercritical Co2mentioning
confidence: 99%
“…24 shows the TGA curves of two PLA samples without POSS, one is unprocessed and the other is pure scCO2 processed, and two PLA samples, one processed with F-POSS-CO2 solution and the other processed with octaisobutyl POSS-CO2 solution. All the processed samples were processed for 3 hours at 323K and 13.8 MPa.…”
mentioning
confidence: 99%
“…Among supercritical fluids, carbon dioxide is the most commonly used supercritical fluid because of nontoxic, nonflammable nature of carbon dioxide. Furthermore, carbon dioxide is relatively inexpensive and it has reasonable critical properties (Tc=304.2 K and Pc=73.8 bar) [1][2][3][4]. The most important thermo-physical property in the supercritical extraction process is the solubility of solutes in supercritical fluid.…”
Section: Introductionmentioning
confidence: 99%